2021
DOI: 10.1021/acs.jcim.1c00853
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cysteine Oxidation in SARS-CoV-2 Receptor-Binding Domain on Its Interaction with Two Cell Receptors: Insights from Atomistic Simulations

Abstract: Binding of the SARS-CoV-2 S-glycoprotein to cell receptors is vital for the entry of the virus into cells and subsequent infection. ACE2 is the main cell receptor for SARS-CoV-2, which can attach to the C-terminal receptor-binding domain (RBD) of the SARS-CoV-2 S-glycoprotein. The GRP78 receptor plays an anchoring role, which attaches to the RBD and increases the chance of other RBDs binding to ACE2. Although high levels of reactive oxygen and nitrogen species (RONS) are produced during viral infections, it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 65 publications
1
15
0
Order By: Relevance
“…MD simulations and MM/PBSA calculations revealed that the formation of disulfide bonds, prevalent during oxidative stress, created a conformation more ready to bind to the receptor, which offered future clues for alternate therapeutic possibilities. 497 Similar work was also performed by Ghasemitarei et al 498 One interesting study performed MM/PBSA calculations to reveal the binding affinities of SARS-CoV-2 S protein to the ACE2s from different species. 499 , 500 This study showed that chimpanzees’ binding affinity was even higher than humans, cats, pangolin, dogs, and monkeys, and chimpanzees had a similar affinity to humans, which suggested some mammals were also vulnerable to SARS-CoV-2.…”
Section: Methods and Approachesmentioning
confidence: 74%
“…MD simulations and MM/PBSA calculations revealed that the formation of disulfide bonds, prevalent during oxidative stress, created a conformation more ready to bind to the receptor, which offered future clues for alternate therapeutic possibilities. 497 Similar work was also performed by Ghasemitarei et al 498 One interesting study performed MM/PBSA calculations to reveal the binding affinities of SARS-CoV-2 S protein to the ACE2s from different species. 499 , 500 This study showed that chimpanzees’ binding affinity was even higher than humans, cats, pangolin, dogs, and monkeys, and chimpanzees had a similar affinity to humans, which suggested some mammals were also vulnerable to SARS-CoV-2.…”
Section: Methods and Approachesmentioning
confidence: 74%
“…In contrast, a superficial mode-of-action is more likely in virions. Here, it is conceivable that an oxidative modification, e.g., of theSARS-CoV-2 spike protein, occurs comparably quickly and might therefore inhibit receptor recognition and the cell membrane fusion process [35] Consistent with this idea, it was reported that the high susceptibility of viruses to PDI is not only caused by reduced structural integrity of viral RNA and virion membranes, but by loss of their surface glycoproteins, leading to non-infectious "bald" virions [18]. Since SARS-CoV-2 requires an envelope homotrimeric spike glycoprotein (S) to interact with the cellular receptor ACE-2 [36], it was proposed that selective impairment of surface proteins, like spike glycoprotein (S), by PDI can effectively inhibit infectivity of SARS-CoV-2 [24,25,37].…”
Section: Discussionmentioning
confidence: 99%
“…As previously described, viruses such as SARS-CoV-2 highjack host cell machinery and establish favorable conditions for viral replication via the increase in oxidative stress caused by an excess of RONS and a deficiency of antioxidants [196]. This oxidative environment favors the binding of the SARS-CoV-2 spike protein to ACE2 [197]. Thereby, targeting oxidative stress by modulating the sensitive redox pathways to regulate the immune response represents a promising therapeutic approach to fighting SARS-CoV-2 infection.…”
Section: Oxidative Stress and Antioxidants In Sars-cov-2 And Potentia...mentioning
confidence: 93%